Pengaruh Media Baru Pembelajaran Terhadap Metode Belajar Online Di Musim Pandemi Covid 19 Pada FISIP UKIM Ambon - Amelia Tahitu; Yoma Souhuwat (JURNAL BADATI, 2022)
This research is entitled the influence of new learning media on online learning methods at the Faculty of Social and Political Sciences, Indonesian Christian University, Maluku Ambon. The problem of this research is to find out how the influence of new learning media on online learning methods in the Covid-19 pandemic season on FISIP UKIM Ambon. This study aims to find out and analyze how the influence of new learning media on online learning methods in the Covid-19 pandemic season on FISIP UKIM Ambon. This research is important to do considering that the learning process in higher education, especially in the study program is an urgent matter and must be the responsibility of the lecturer to students face-to-face in class. However, given the outbreak of Covid-19, the learning process is carried out through the onine learning method. To find out the research problem about the influence of new learning media on online learning methods in the Covid-19 pandemic season on FISIP UKIM Ambon, and adjusted to the objectives and benefits of the research, this study uses quantitative methods. The results of the study with statistical tests can be explained that, new media of learning with measuring indicators, namely; software, internet networks, google classroom, and zoom meetings have a significant effect on online learning methods. It is based on the t Test which means that the hypothesis is accepted. And based on the Value Determination Test ( r2 ) shows that 21.8% of the influence of online learning methods at FISIP UKIM (Y) is influenced by new learning media (X). While the remaining 78.2% was described or influenced by other indicators not studied in this study. Variable Y with measuring indicator; learning / science delivery strategies, and learning management have a significant effect on variable X so that hypothesis results are accepted.